A STUDY OF INDIA- SEYCHELLES MARITIME SECURITY COOPERATION - Shukla, Smriti; Ahmad, Mohammad Wasim (ShodhKosh: Journal of Visual and Performing Arts, 2024)
In the 21st century, India’s foreign policy strongly emphasizes the Indian Ocean Region (IOR). As a result, the Island States in the IOR are receiving special attention. Seychelles, among many other Islands, is critical to India’s role in the IOR as a net security provider (NSP). India and Seychelles seek to expand their bilateral relationship through collaboration in maritime security. Relations between India and the Seychelles began in 1976, the same year as the Seychelles’ independence. Seychelles is an important partner in India’s much-heralded SAGAR and an ally in the Western Indian Ocean region (WIOR). Given that the IOR is strategically India’s backyard, and is home to important global sea lanes for communications, both traditional and non-traditional threats have grown more severe, thus necessitating extensive bilateral and regional cooperation. Seychelles is navigating through the tough water of balancing between India and China in various strategic issues like that of the Assumption Islands. The region is suffering from non-traditional issues of piracy, illegal fishing, disaster, and irregular migration. Acting as the NSP – India in the past and present has reached out to its partner states through political, economic, and defense alliances. Yet the potential for ensuring comprehensive maritime security cooperation (MSC) is much more and the new academic tilt towards the Indo-Pacific is enriching the Indian Ocean region with multiple state actors. Therefore, the objective of the paper is to analyze various facets of India and Seychelles’ MSC and its impact on both nation-states. The methodology adopted is descriptive in presenting the history of bilateral MSC between these nation-states and analytical in understanding challenges faced by these nation-states in the current world order and the impact of India-Seychelles MSC in resolving such challenges.